High molecular weight fibroblast growth factor 2 induces apoptosis by interacting with complement component 1 Q subcomponent–binding protein in vitro. Issue 11 (29th August 2018) - Hong, Xiaobing; Yu, Zelin; Chen, Zhonglin; Jiang, Hongyan; Niu, Yongdong; Huang, Zhanqin
Abstract: Fibroblast growth factor 2 (FGF2) is a multifunctional cell growth factor that regulates cell proliferation, differentiation, adhesion, migration, and apoptosis. FGF2 has multiple isoforms, including an 18‐kDa low molecular weight isoform (lo‐FGF2) and 22‐, 23‐, 24‐, and 34‐kDa high molecular weight isoforms (hi‐FGF2). Hi‐FGF2 overexpression induces chromatin compaction, which requires the mitochondria and leads to apoptosis. Complement component 1 Q subcomponent–binding protein (C1QBP) plays an important role in mitochondria‐dependent apoptosis by regulating the opening of the mitochondrial permeability transition pore. However, the interaction between C1QBP and hi‐FGF2 and its role in hi‐FGF2–mediated apoptosis remain unclear. Here, we found that hi‐FGF2 overexpression induced depolarization of the mitochondrial membrane, cytochrome c release into the cytosol, and a considerable increase in C1QBP messenger RNA and protein expression. Furthermore, coimmunoprecipitation results showed that the mitochondrial protein, C1QBP, interacts with hi‐FGF2. C1QBP knockdown using small interfering RNA significantly decreased the localization of hi‐FGF2 to the mitochondria and increased the rate of apoptosis. Our results highlight a novel mechanism underlying hi‐FGF2–induced, mitochondria‐driven cell death involving the direct interaction between hi‐FGF2 and C1QBP and the upregulation of C1QBP expression. Abstract : hi‐FGF2 can induce mitochondria‐associated apoptosis in HEK293 cells. This may be due to the upregulated C1QBP expression and direct interaction with C1QBP, resulting in the depolarization of mitochondria and a corresponding cytochrome c release.